A CASE REPORT : Komplikasi dan Tatalaksana Snakebite: Komplikasi dan Tatalaksana Snakebite - IDA BAGUS ADITYA NUGRAHA (Yayasan Pendidikan Medika Indonesia, 2022)
Indonesia as one of the largest tropical and agricultural countries in the world shared the particularly high burden cases of snakebite. The clinical manifestations of snakebite could vary according to the type of venoms. This case reported a 75 years old male patient with snakebite in Pedis Sinistra come with bleeding and anuria. Bleeding caused by snake venom is presenting with blood clotting disturbances as the result of venom-induced consumption coagulopathy (VICC). VICC, a disseminated intravascular coagulation (DIC)-like syndrome, is characterised by low levels or undetectable of fibrinogen, resulting in incoagulable blood. Renal manifestations vary from urinary sediment changes with mild proteinuria to renal failure. Nephropathy in snakebite is the result of several mechanisms including the inflammatory process, direct nephrotoxicity, and immunologic reaction. Appropriate first aid treatment and comprehensive management of snakebite cases are warranted to reduce mortality and morbidity rates. The patient was diagnosed with VICC and acute kidney injury (AKI) related snakebite. The patient was applied pressure immobilization bandage, given antivenom, fresh frozen plasma (FFP), thrombocyte concentrate (TC), antibiotic, and renal replacement theraphy. After the treatment, bleeding was improved, but after iatrogenic pnemothorax and pneumonia occured, the patient's condition deteriorated. Unfortunately, the patient has died on 13rd day of treatment with causa mortis multiple organ failure.